Pengembangan Cash Management System (CMS) Berbasis Web Berbasis Cash Processing Center (CPC) di PT. XYZ - Andriana Suhendi; Vina Ayumi (JSAI (Journal Scientific and Applied Informatics), 2025)
This research aims to develop a web-based financial management system to optimize cash management at PT. XYZ. The background of this research is based on the importance of utilizing technology to support the operations of cash management service companies, such as PT. XYZ, which handles Cash In Transit (CIT) and Cash Management. With the rapid advancement of technology, an application is needed that can simplify cash management processes, improve efficiency, and reduce the risk of errors in recording daily transactions. The research methodology used is qualitative, involving active participation, observation, interviews, and documentation. The researcher directly participated in the application development process with the CPC division for 3 months, observing workflows and system requirements, and discussing with employees and company management. Interviews were conducted to understand managerial needs, while observations focused on monitoring existing cash management operations as the basis for developing a new system. The research results show that the development of the web-based financial management system successfully optimized the recording of cash inflows and outflows, facilitated customer data management, and ensured operational efficiency.